2009
DOI: 10.1159/000224339
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone-Induced Increases in Skeletal Muscle Mass Alleviates the Associated Insulin Resistance in Short Children Born Small for Gestational Age, but Not with Growth Hormone Deficiency

Abstract: Purpose: To assess the effect of growth hormone (GH) treatment on body composition and insulin resistance, and the interdependence of these factors, in short children born small for gestational age (SGA) and children with growth hormone deficiency (GHD). Methods: In this longitudinal study we describe the relationship between changes in fasting hormone levels, and forearm cross-sectional fat/muscle area in 54 short children with GHD and 37 short children born SGA during the first 12 months of GH treatment. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
1
4
2
Order By: Relevance
“…A transient increase from baseline in mean fasting glucose was noted with the 0.7 mg/kg/wk dose of LB03002 and in mean HbA1c with the 0.5 mg/kg/wk dose although not with the higher dose of 0.7 mg/kg/wk. Although there have been concerns of a potential effect of GH administration on glucose homeostasis (22), there is little evidence for a negative effect in GH-treated children unless other risk factors are present (23,24). The current study did not indicate an increased risk of impaired glucose metabolism with LB03002 administration over 36 months.…”
Section: Discussioncontrasting
confidence: 59%
“…A transient increase from baseline in mean fasting glucose was noted with the 0.7 mg/kg/wk dose of LB03002 and in mean HbA1c with the 0.5 mg/kg/wk dose although not with the higher dose of 0.7 mg/kg/wk. Although there have been concerns of a potential effect of GH administration on glucose homeostasis (22), there is little evidence for a negative effect in GH-treated children unless other risk factors are present (23,24). The current study did not indicate an increased risk of impaired glucose metabolism with LB03002 administration over 36 months.…”
Section: Discussioncontrasting
confidence: 59%
“…In our patients we saw a clear increase of insulin levels within the normal range (table 3). Martin et al [26] have shown that in the short term increase in muscle mass and decrease in fat mass was inversely related to increase in insulin resistance in short children born SGA undergoing GH treatment. None of the known side effects of GH were observed in the children of this study.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon would perhaps deserve further study in a meta-analysis of a large number of GH studies. From our previous studies we would expect slightly lower height velocities of about 5.5 ± 1 cm/year (-0.55 ± 1 SDS) at GH start in short children born SGA [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Findings on the effects of GH therapy on body composition in included studies are summarized in Table 2. Treatment with GH is associated with a substantial reduction in adipose tissue mass and an increase in lean body mass (LBM) [109][110][111][112][113][114]. This leads to a normalization of BMI [109].…”
Section: Effects Of Gh Therapy On Body Compositionmentioning
confidence: 99%